The Exploratory and Confirmatory Factorial Structure of Test-Wiseness Scale: A Field Study on a Sample of Students in Hama University (Journal of the College of Education for Women, 2022)
The current research aims to recognize the exploratory and confirmatory factorial structure of the test-wiseness scale on a sample of Hama University students, using the descriptive method. Thus, the sample consists of (472) male and female students from the faculties of the University of Hama. Besides, Abu Hashem’s 50 item test-wiseness scale (2008) has been used. The validity and reliability of the items of the scale have also been verified, and six items have been deleted accordingly. The results of the exploratory factor analysis of the first degree have shown the presence of the following five acceptable factors: (exam preparation, test time management, question paper handling, answer sheet handling, and revision). Moreover, (63.391%) of the overall variance has been explained. By conducting the second degree of the factorial analysis of the five factors, it has been shown that there is one main factor that is acceptable. Its eigenvalues are (2.821). In addition, (56.429%) of the overall variation has been illustrated and identified as a factor (test-wiseness). The results of the confirmatory factor analysis have also revealed that there is a congruence between the supposed model and the realistic model, and that the 44 item test-wiseness scale in its modified Syrian form is characterized by its high indicators of validity (content validity, structural validity, discriminative validity) and reliability (split half, internal consistency using Cronbach's alpha coefficient).